Managing Brand Equity : A Case Study of PT. X - Vincent Effendi; Joseph Shalom Liemmongan (iBuss Management, 2017)
Food & beverages is a tremendously growing industry in the recent and future years. It is a heavy and competitive industry with a steep prospect for Entrepreneurs in Surabaya. This research explore an immense opportunity to explore the impact of having a brand equity towards the purchase intention of F&B’s industry for the case of PT. X.This Case Study found that there are discrepancies and similarities in the perspective of Owners/Brand Managers of PT. X and their consumers in influencing the purchase intention by Brand Equity. Employing both qualitative (interviews) and quantitative (self-administered questionnaires) the research found that the similarities are on perceived quality and brand loyalty, while the different findings are in the brand awareness and brand association; the owner/brand managers thought that the variables is affecting well, while the results do not show like what they perceived. The owners comes up with different factors from the brand equity’s elements in affecting purchase intention in responding to the consumers’ perception, which is, ‘Trend’ and Appetite. In the statistical methods, specific individual elements that are significant are: Perceived Quality, and Brand Loyalty, while Brand Awareness and Brand Association were not. Keywords:  Brand Equity, Purchase Intention, Branding Management, Marketing Management